2021
DOI: 10.1186/s12938-020-00840-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of muscle activity using electrical stimulation and mechanomyography: a systematic review

Abstract: This research has proved that mechanomyographic (MMG) signals can be used for evaluating muscle performance. Stimulation of the lost physiological functions of a muscle using an electrical signal has been determined crucial in clinical and experimental settings in which voluntary contraction fails in stimulating specific muscles. Previous studies have already indicated that characterizing contractile properties of muscles using MMG through neuromuscular electrical stimulation (NMES) showed excellent reliabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 84 publications
(59 reference statements)
0
22
0
Order By: Relevance
“…By using the waveform data or epoch from the specific user, it is also possible to eliminate some of the factors that affect the ErrP morphology. Age has consistently been reported to reduce the ErrP amplitude (see, e.g., [ 57 ]), and factors such as the perceived severity of the error [ 16 ], awareness of error [ 41 , 58 ], and error type modulate the ErrP morphology [ 16 , 59 , 60 ]. The latter factors in particular may be more pronounced in individuals with stroke compared with able-bodied individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the waveform data or epoch from the specific user, it is also possible to eliminate some of the factors that affect the ErrP morphology. Age has consistently been reported to reduce the ErrP amplitude (see, e.g., [ 57 ]), and factors such as the perceived severity of the error [ 16 ], awareness of error [ 41 , 58 ], and error type modulate the ErrP morphology [ 16 , 59 , 60 ]. The latter factors in particular may be more pronounced in individuals with stroke compared with able-bodied individuals.…”
Section: Discussionmentioning
confidence: 99%
“…As outlined previously, in this application ErrPs could be used to maintain good BCI performance by alleviating the effect of fatigue. Some studies have shown that ErrPs can be elicited in people with stroke [ 41 , 42 , 43 ], brain lesions [ 44 , 45 , 46 , 47 , 48 , 49 ], and traumatic brain injuries [ 50 ], but there is some variability in the ErrP morphology known from healthy volunteers. Generally, this is manifested through smaller or attenuated peak amplitudes.…”
Section: Introductionmentioning
confidence: 99%
“…However, a new generation of FEHM consider the nonlinear behavior and viscoelasticity of brain structures, as it has been explicitly pointed out by the developers of YEAHM (University of Aveiro) [ 50 ]. Interestingly, some FEHM model CBVs as nonlinear elastic materials [ 51 , 52 , 53 ], and some of these models use curves and fittings based on [ 19 , 31 ]. These new models include geometric details of the vasculature and even consider the internal pressure inside the CBVs.…”
Section: Discussionmentioning
confidence: 99%
“…It is typically a high-grade malignancy with a rapid growth rate. The etiology of OS is multifaceted and poorly understood [ 2 , 3 ]. Conventional OS is the most frequent histologic type and accounts for about 75% of all cases.…”
Section: Introductionmentioning
confidence: 99%
“…It has an annual incidence rate of approximately 3.1 cases per million in the United States, accounting for less than 1% of all newly diagnosed cancers in adults and 3–5% of those in children. Although rare, it is the most common primary malignancy in adolescents outside leukemia and lymphoma, and the most common primary malignancy of bone in children [ 3 , 4 , 5 , 6 ]. Prior to the advent of chemotherapy, OS was generally a fatal disease although over the last 30 years, no significant improvements were achieved for metastatic OS [ 7 ].…”
Section: Introductionmentioning
confidence: 99%